A Study of the Efficiency and Unbiasedness in NCDEX: A Case Study of Guar Gum - Soni, Tarun K.; Singla, Harish K. (Indian Journal of Finance, 2013)
The paper aims to study the market efficiency and unbiasedness among guar gum futures contracts traded at the National Commodity&Derivatives Exchange Ltd. (NCDEX). The study has tested the market efficiency and unbiasedness with different maturities using cointegration analysis, and short-term market efficiency, using an error correction model and GARCH-M-ECM. The results suggest that the futures market for guar gum is inefficient in both short run and long run for all maturity periods, which may be caused by over-speculation or market manipulation. The results indicate an urgent need to provide more powers to FMC to regulate the market and penalize any insider trading, cartelization, and price manipulations.